2017
DOI: 10.1111/1475-6773.12680
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Disease Prevalence Adjustment on Hospitalization Rates for Chronic Ambulatory Care–Sensitive Conditions in Germany

Abstract: Unadjusted ACSH rates should be used with caution for high-stakes public reporting as differences in prevalence may have a marked impact. Prevalence adjustment should be considered in models analyzing ACSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
14
0
2
Order By: Relevance
“… 15 And while individual comorbidities are a major predictor of ACSCs, 16 , 17 even area-level disease prevalence explains variation in ACSC rates. 18 Shorter travel time to PHC reduces ACSCs rates, 9 , 19 while shorter travel time to hospitals, 19 high rurality, 20 and high hospital bed supply 12 , 21 , 22 increase them.…”
mentioning
confidence: 99%
“… 15 And while individual comorbidities are a major predictor of ACSCs, 16 , 17 even area-level disease prevalence explains variation in ACSC rates. 18 Shorter travel time to PHC reduces ACSCs rates, 9 , 19 while shorter travel time to hospitals, 19 high rurality, 20 and high hospital bed supply 12 , 21 , 22 increase them.…”
mentioning
confidence: 99%
“…Eight studies were excluded, because they used ICD codes only (Albrecht et al 2016 [14]; Fortin et al 2017 [15]; Schwarzkopf et al 2016 [16]), or because they only reported the study protocol (Josephs et al 2017 [17]), or because they did not differentiate between asthma and COPD (Marrie et al 2016 [18]; Oelsner et al 2016 [19]). One publication was excluded, because it duplicated another publication (Vozoris et al 2016 [20]), and one study was excluded, because it investigated a different disease (Pollmanns et al 2018 [21]). Finally, 38 studies were included in the review as one study was identified by hand search.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, claims data are primarily collected for reimbursement purposes and not for morbidity estimation and are known to overestimate the true epidemiological prevalence, in particular, if a case definition is only based on a single diagnosis. Previous research on asthma and COPD based on routine data thus applies a more conservative case definition 21,22,[31][32][33] . Furthermore, per case definition (i.e., diagnoses in at least two different quarters), patients with concurrent asthma/COPD diagnoses have higher rates of health care contacts, in particular, if patients visit different physicians as compared to controls.…”
Section: Strengths and Limitationsmentioning
confidence: 99%